1998
DOI: 10.1128/iai.66.6.2420-2425.1998
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Characterization of the Stability of the 150-Kilodalton Botulinum Toxin, the Nontoxic Component, and the 900-Kilodalton Botulinum Toxin Complex Species

Abstract: Botulinum neurotoxin serotype A is initially released from the bacterium Clostridium botulinum as a stable 900-kDa complex. The serotype A 900-kDa complex is one of the forms of the toxin being used as a therapeutic agent for the treatment of various neuromuscular disorders. Previous experiments have demonstrated that the 900-kDa complex form of the toxin protects the toxin from the harsh conditions of the gastrointestinal tract. To provide molecular level details of the stability and equilibrium of the 900-kD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…Because the large TCs exhibit significantly higher oral toxicity than pure BoNT, the auxiliary nontoxic proteins have been considered essential for food poisoning (Sakaguchi et al, 1984). Although their most accepted function is as a safeguard against the harsh conditions in the digestive tract (Halliwell, 1954;Ohishi et al, 1977;Sugii et al, 1977a, b;Bonventre, 1979;Ohishi & Sakaguchi, 1980;Ohishi, 1984;Chen et al, 1998;Niwa et al, 2007), the role of the nontoxic proteins is still under debate. There is some evidence that the HA components of auxiliary nontoxic proteins play a role in absorption across the intestinal epithelium (Fujinaga et al, 1997(Fujinaga et al, , 2004Nishikawa et al, 2004;Uotsu et al, 2006;Niwa et al, 2007Niwa et al, , 2010.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the large TCs exhibit significantly higher oral toxicity than pure BoNT, the auxiliary nontoxic proteins have been considered essential for food poisoning (Sakaguchi et al, 1984). Although their most accepted function is as a safeguard against the harsh conditions in the digestive tract (Halliwell, 1954;Ohishi et al, 1977;Sugii et al, 1977a, b;Bonventre, 1979;Ohishi & Sakaguchi, 1980;Ohishi, 1984;Chen et al, 1998;Niwa et al, 2007), the role of the nontoxic proteins is still under debate. There is some evidence that the HA components of auxiliary nontoxic proteins play a role in absorption across the intestinal epithelium (Fujinaga et al, 1997(Fujinaga et al, , 2004Nishikawa et al, 2004;Uotsu et al, 2006;Niwa et al, 2007Niwa et al, , 2010.…”
Section: Discussionmentioning
confidence: 99%
“…The TCs (M-TC, L-TC and LL-TC) display greater oral toxicity than pure BoNT (Ohishi et al, 1977;Sakaguchi et al, 1984). Pure BoNT without auxiliary nontoxic components is susceptible to the proteolytic and acidic conditions in the digestive tract (Halliwell, 1954;Ohishi et al, 1977;Sugii et al, 1977a, b;Bonventre, 1979;Ohishi & Sakaguchi, 1980;Ohishi, 1984;Chen et al, 1998;Niwa et al, 2007), indicating that the nontoxic components serve to protect BoNT against the conditions of the gastrointestinal tract. There is evidence that the L-TC transports across the intestinal epithelial cell monolayer more effectively than pure BoNT (Fujinaga et al, 1997(Fujinaga et al, , 2004Niwa et al, 2007, 2010; Inui et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This structure appears to have a protective function after ingestion, shielding the neurotoxin from acidic stomach conditions and thermal and pH stress. [8][9][10] It has also been suggested that the natural complex acts as a shield for the antigenic epitopes on the 150-kD heavy chain 11 and facilitates BoNTA transfer across the intestinal epithelium. [12][13][14][15] In medicine, the effect and role of the complex's size and composition are not clear and remain controversial.…”
Section: The Science Of Bontmentioning
confidence: 99%
“…BoNTA is naturally produced as a complex of a core neurotoxin protein, along with several hemagglutinin and nontoxin nonhemagglutinin proteins 3,5 . The associated proteins serve to stabilize and protect the neurotoxin molecule from degradation 6,7 …”
Section: Introductionmentioning
confidence: 99%